Identification of some nucleotide mutations in Waxy gene (BGIOSGA022241) of a mutant rice line - Nguyen Thi, Hong; Yoshikazu, Tanaka; Vo Thi, Minh Tuyen; Le, Huy Ham (Nuclear Science and Technology, 2018)
Waxy genes of the original variety and its mutant type were sequenced by Sanger method and compared through Nucleotide Basic Local Alignment Search Tool (BLASTN) to clarify differences. BLASTN result showed four nucleotide mutations in coding regions and 59 nucleotide mutations in noncoding regions. Four point mutations in coding regions were: the deletion of T/- at position 34 and the insertion of -/T between positions 70 and 71 in exon 3; the substitution of C/T at position 14 in exon 4 and the substitution of T/C at position 115 in exon 9. In 59 mutant nucleotides in non-coding regions, some significant alterations were list: the deletion of nucleotide G at the first of intron 6 and the addition of 32 nucleotides “GGGCCTGCGAAGAACTGGGAGAATGTGCTCCT” at the end of intron 12. For the first trial, a new DNA marker was developed based on the mutation C/T at at position 14 in exon 4 and the substitution of T/C at position 115 in exon 9 to improve efficiency of rice breeding relevant to Waxy gene.